In silico and in vitro analysis primers for antibiotic resistance gene of bacteria - Eva Ayuntya; Kiky Martha Ariesaka; Wahyu Prihanta; Husamah Husamah; Fendy Hardian Permana; Moh Mirza Nuryady (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2025)
The prevalence of Extended-Spectrum Beta-Lactamase (ESBL) occurs due to excessive use of antibiotics, resulting in antibiotic resistance. Research on ESBL has been conducted in several Indonesian cities, such as Surabaya, Malang, and Jakarta which identified the presence of ESBL bacterial isolates. Limited information about blaCTX-M and blaVEB primer data in in silico analysis such as primer length, GC base content, melting temperature, and organisms attached to the gene, is an important thing that needs further research, because in silico data will affect the annealing temperature in the in vitro process using Polymerase Chain Reaction (PCR). The purpose of this study was to determine that blaCTX-M and blaVEB primers can be used to detect the presence of ESBL genes from amplification results in PCR. In silico primer analysis was carried out using BLAST primers from the NCBI website which would then be continued through in vitro primer analysis using PCR to see the presence of DNA bands. The results of in silico research showed that there were 27 organisms detected in the blaCTX-M gene and 37 organisms in the blaVEB gene. The results of in vitro analysis on blaCTX-M primers can be amplified at ± 400 bp, while blaVEB cannot be amplified.